1986
DOI: 10.1227/00006123-198610000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Relations of the Trigeminal Nerve: An Anatomical Study

Abstract: The neurovascular relationships in the trigeminal root entry zone were studied in 130 trigeminal root entry zones of 65 cadavers. No history of facial or trigeminal pain had been obtained during life in these subjects. The technique of intravascular injection, which allowed good visualization and evaluation of the neurovascular relationships, is described. A total of 42 examples of contact with the root entry zone and 10 examples of compression were identified. In 30 of the examples of contact, the finding cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 0 publications
2
23
0
3
Order By: Relevance
“…3,8,9,11 All these arteries have the potential to cause trigeminal neuralgia. Nerve compression is often caused by a combination of vessels, including various veins, and the offending vessel may not be definitively identified during the operation.…”
Section: Discussionmentioning
confidence: 99%
“…3,8,9,11 All these arteries have the potential to cause trigeminal neuralgia. Nerve compression is often caused by a combination of vessels, including various veins, and the offending vessel may not be definitively identified during the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we do not have the information about the history of TGN in these humans analogously as in the previous publication. In the other anatomical study, Klun and Prestor [12] examined 130 specimens (65 heads) and observed 42 examples of contact and 10 instances of compression of the vessels with the REZ of the V th nerve. In the analysed group, 30 conflicts were related to arterial vessels (53.8% -SCA, 25.6% -AICA, 20.6% -the pontine branches of BA), 11 may have components of the vein, and only 1 anatomical specimen with unequivocal compression by vein vessel was found [12].…”
Section: Analysis Of the Anatomical Variations Of Neurovascular Conflictmentioning
confidence: 99%
“…The percentage is approximately 0-28%, and it depends on the number of microdecompression series [1,11,17,21,23,25,30]. It is the cause why they have concluded that vascular compression may be the predominant, but not the sole cause of TGN and the pathophysiology of pain is still unclear [12,21,23]. trigeminocerebellar artery, which is the branch of BA lying between V th nerve and the hemisphere of cerebellum.…”
Section: Analysis Of the Anatomical Variations Of Neurovascular Conflictmentioning
confidence: 99%
“…Fibers arising from the motor nucleus emerge from the ventral surface of pons forming the motor root of the mandibular nerve which lies anteromedial to the sensory root. The sensory root may be compressed by the superior cerebellar , anterior inferior cerebellar, or pontine branches of basilar artery which may be important in trigeminal neuralgia (11,12).…”
Section: Functional Components Of Mandibular Nerve and Their Intraneumentioning
confidence: 99%